Improvement of the impact strength of ethylene‐propylene random copolymers by nucleation. Issue 34 (18th May 2016) - Horváth, Zsuzsanna; Menyhárd, Alfréd; Doshev, Petar; Gahleitner, Markus; Friel, David; Varga, József; Pukánszky, Béla
ABSTRACT: Five ethylene‐propylene random copolymers were nucleated with two soluble nucleating agents. Ethylene content changed between 1.7 and 5.3 wt %, while nucleating agent content was adjusted according to the solubility of the additive. It changed from 0 to 5000 ppm for the sorbitol (1, 2, 3‐tridesoxy‐4, 6:5, 7‐bis‐O‐[(4‐propylphenyl) methylene]‐nonitol) and from 0 to 500 ppm for the trisamide compound (1, 3, 5‐benzene‐trisamide) used. Crystalline structure was analyzed in detail by various methods (DSC, XRD, and SEM). Mechanical properties were characterized by tensile and instrumented impact measurements. The results showed that most properties changed moderately upon nucleation, but impact resistance increased considerably. Spherulitic structure was not detected, but instead in the presence of the soluble nucleating agents used a microcrystalline structure formed. The large increase of impact resistance could not be related directly to changes in crystalline morphology. On the other hand, local rearrangement of morphology was detected by XRD and SEM analysis including an increase of lamella thickness, crystal orientation, and the formation of shish‐kebab structures in the core of the injection molded specimens. A small increase in the γ‐phase content of PP was also observed. These changes increased crack propagation energy considerably leading to the large improvement observed in impact resistance. Although the phenomenon could be related to ethylene content, differences in molecular weight also helped to explain the changes observed. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43823. Abstract :